An experimental investigation of flow boiling heat transfer and pressure drop of R134a in a horizontal 2.168 mm tube under hypergravity. Part II: Heat transfer coefficient. (January 2015) - Xu, Yu; Fang, Xiande; Li, Guohua; Li, Dingkun
Abstract: An experimental study on flow boiling of R134a under hypergravity is conducted for assessing the effect of gravity on two-phase flow boiling heat transfer coefficient. The experiments were conducted with a horizontal smooth copper tube with an inner diameter of 2.168 mm under both hypergravity (1.12–3.16 g) and normal gravity (1 g), with mass flux of 725 and 910 kg/m 2 s, heat flux of 19.0 and 28.5 kW/m 2, saturation pressure of 0.71 and 0.82 MPa (saturation temperature of 27.2 and 32.2 °C), and vapor quality from 0 to 0.65. The hypergravity environment was generated with a centrifugal acceleration machine. The experimental data under hypergravity are compared with those under normal gravity and with the predictions of 11 outstanding existing correlations developed for normal gravity. The results indicate that the heat transfer coefficient under hypergravity is greater than that under normal gravity and increases with increasing hypergravity. The best existing correlation developed for normal gravity has the mean absolute deviation of 14.2% against the experimental data in the hypergravity range.